2020
DOI: 10.1111/aji.13381
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic cytokine and interleukin 8 levels in early luteal phase after triggering ovulation with gonadotropin‐releasing hormone agonist in high‐responder patients

Abstract: Ovarian hyperstimulation syndrome (OHSS) is the most common complication of assisted reproductive technology (ART). 1 Ovarian hyperstimulation syndrome is characterized by the increased vascular permeability, fluid leakage into the third space, and may result in hemoconcentration. 2 While mild OHSS usually has a temporary nature and limited clinical relevance, severe OHSS is characterized by the substantial ovarian enlargement, pleural effusion, ascites, hemoconcentration, oliguria, and, potentially, thromboem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In the present study, we found a comparable late-onset OHSS in group I and the control group (with a full dose of hCG). Our previous results demonstrated that any dose of hCG caused a similar VEGF concentration in the blood, even when the GnRH agonist had been added for oocyte triggering, which could have resulted in OHSS (13) and supported the present conclusion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, we found a comparable late-onset OHSS in group I and the control group (with a full dose of hCG). Our previous results demonstrated that any dose of hCG caused a similar VEGF concentration in the blood, even when the GnRH agonist had been added for oocyte triggering, which could have resulted in OHSS (13) and supported the present conclusion.…”
Section: Discussionsupporting
confidence: 90%
“…The authors conclude that some form of LH supplementation after the GnRHa trigger may be necessary for corpus luteum support and in-vitro fertilization (IVF) success in high-risk patients with peak E2 <4,000 pg/ml ( 11 ). However, the LH/hCG supplementation in high-responder patients could increase the risk of OHSS development ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…VEGFR2 is believed to act as the chief receptor in enhancing endothelial permeability by the breakdown of cell-cell contact which eventually leads to OHSS ( 57 ). While comparable levels of VEGFA were demonstrated in GnRH-a with hCG as LPS, dual trigger, and hCG triggered cycles during OPU+5, VEGF-A was significantly lower in GnRH-a with hCG as LPS cycles during OPU when compared to hCG triggered cycles ( 56 ).…”
Section: Discussionmentioning
confidence: 89%
“…The purpose of several methods is to strike a balance between levels of VEGF-A and P that allows normal implantation and neovascularization to take place but are not sufficient to produce clinical symptoms of OHSS. The use of hCG as LPS at OPU in GnRH-a triggered patients has shown non-significant marginally increased rates of OHSS when compared to dual trigger group ( 55 ) while producing significantly lower concentrations of VEGF-A to a full dose of hCG at OPU ( 56 ). The decrease in the incidence of OHSS in both GnRH-a with hCG as LPS and dual triggered cycles can be attributed to significantly lower levels of vascular endothelial growth factor receptor 2 (VEGFR2) during both OPU and OPU+5 days when compared to hCG triggered cycles ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation